Influence of Radio Frequency Magnetron Sputtering Parameters on the Structure and Performance of Al and Al2O3 Thin Films - Blazquez, R. Ramos; Solis-Pomar, Francisco; Fundora, Abel; Ruiz-Roblez, Mitchel A.; Fragiel, Amilkar; Perez-Tijerina, Eduardo (East European Journal of Physics, 2025)
In this work, the structural, morphological and optical properties of aluminum (Al) and aluminum oxide (Al₂O₃) thin films deposited by radio-frequency (RF) magnetron sputtering were studied. The films were grown using a high–purity Al target in controlled atmospheres containing varying flows of argon (Ar) and oxygen (O₂). Particular attention was given to how the target-substrate distance and the Ar/O2 flow ratios influence the films’ structural properties, surface features, and optical response. Characterization techniques included X-ray diffraction (XRD) for phase identification and crystallite size estimation, Atomic Force Microscopy (AFM) for surface morphology and roughness analysis, and UV–Vis Spectroscopy for optical transmittance measurements. The results showed that reducing the target-substrate distance led to films with increased surface roughness, thickness, grain size and crystallite size, likely due to enhanced energetic bombardment and adatom mobility. Optical measurements revealed that Al2O3 films grown at higher O2 flow rates (around 5 sccm) were highly transparent, exhibiting transmittance values close to 100% across the UV-visible range (190-900 nm). In contrast, films deposited under low O2 flow conditions (0.6-1.4 sccm) were nearly opaque, indicating incomplete oxidation or metallic behavior. The XRD analysis revealed that higher O2 flows tended to suppress crystallinity, resulting in amorphous Al2O3 films, while lower flows preserved some degree of crystalline order. Additionally, increasing the Ar flow rate during deposition promoted films growth, as evidenced by increased film thickness, which may be attributed to enhanced sputtering efficiency and target atom flux. These findings highlight the critical role of deposition parameters in tailoring the properties of Al-based thin films for optical and electronic applications.